Urban and connected: a profile of the 21st century stingless beekeeper - Ruaro, Eduarda Letícia; Meirelles, Rafael Narciso; Uhlmann, Lauren Nathiely Garcia; Pires, Paola Ramos Simões; Leães, Fernanda Leal (Revista de Ciências Agroveterinárias, 2022)
Bees are responsible for pollination, which is an important ecosystem service. They also provide the production of honey, pollen or saburá, propolis, among other products. The breeding of native bees has been growing, because of the particular characteristics of each species and its products. Therefore, the objective was to know the profile of this breeder, called meliponicultor. Then, a semi-structured questionnaire was used, widely publicized on social networks, in April and May 2020. This was attended by 718 Brazilian and foreign breeders of native bees, of which 80.3% practice the activity as a hobby, most beginners in the activity, with the main objective of leisure and family consumption of honey. Over 80% keep bees in meliponaries in urban areas. Among the products, the swarm is the most commercialized, with species that are easy to handle, less defensive and adapted to the region being preferred. Swarms are also acquired through bait, rescue and division. The bees are created in boxes of different materials, the main one being wood and the tools are easily found in the commerce, as well as easy to improvise. Beekeepers reported concerns about deforestation, increasing urban areas, fires, global warming, pesticides, pest attacks and theft. Digital media was cited as the main source of information, followed by books and close people. The creators also stated that they do not trust 100% the information that reaches them, regardless of the source.